Ascorbate Biosynthesis in Mitochondria Is Linked to the Electron Transport Chain between Complexes III and IV - Bartoli, Carlos Guillermo (2000)
Ascorbic acid is synthesized from galactono-γ-lactone (GL) in plant tissues. An improved extraction procedure involving ammonium sulfate precipitation of membrane proteins from crude leaf homogenates yielded a simple, quick method for determining tissue activities of galactono-γ-lactone dehydrogenase (GLDH). Total foliar ascorbate and GLDH activity decreased with leaf age. Subcellular fractionation experiments using marker enzymes demonstrated that 80% of the total GLDH activity was located on the inner mitochondrial membrane, and 20% in the microsomal fraction. Specific antibody raised against potato (Solanum tuberosum L.) tuber GLDH recognized a 56-kD polypeptide in extracts from the mitochondrial membranes but failed to detect the equivalent polypeptide in microsomes. We demonstrate that isolated intact mitochondria synthesize ascorbate in the presence of GL. GL stimulated mitochondrial electron transport rates. The respiration inhibitor antimycin A stimulated ascorbate biosynthesis, while cyanide inhibited both respiration and ascorbate production. GL-dependent oxygen uptake was observed in isolated intact mitochondria. This evidence suggests that GLDH delivers electrons to the mitochondrial electron transport chain between complexes III and IV.